The Unbalanced Control Research of Fractional-Order Cascaded H-Bridge Multilevel STATCOM - Junhua Xu; Guopeng He; Songqin Tang; Zheng Gong; Chunwei Wang; Yue Lan (Fractal and Fractional)
Recent research on fractional-order cascaded H-bridge multilevel static compensator (FCHM-STATCOM) indicates that it has better performance than the traditional cascaded H-bridge multilevel static compensator (CHM-STATCOM). The existing FCHM-STATCOM control system lacks some special control links for dealing with unbalanced operative situations, which is demanded by power systems. This paper improves the existing FCHM-STATCOM control system to satisfy the demand for power systems, creating the potential for it to be applied in the electrical industry. The improvement of the FCHM-STATCOM control system is based on traditional CHM-STATCOM control systems, introducing special control loops for unbalanced operative situations. The improved FCHM-STATCOM control system constructed in this paper consists of an outer control loop that can apply special strategies for different control objectives, two inner control loops, respectively, for positive- and negative-sequence currents, and an inter-phase balancing control loop for balancing its arm operation. At the end of this paper, the results of digital simulations verify the FCHM-STATCOM complete control system’s capacity to regulate its negative-sequence currents and balance its arm operation to deal with unbalanced operative situations. Moreover, based on different strategies, the control system shows effectiveness in eliminating power oscillations and current balancing.